Primary splenic red pulp diffuse large B-cell lymphoma with anaplastic features - Khandakar, Binny; Wang, Wei; Li, Shaoying (Stem Cell Investigation, 2016)
A 76-year-old man presented with B symptoms, anemia (Hb 11 g/dL), and thrombocytopenia (96,000/µL) with elevated serum LDH (1,916 U/L) and ferritin (4,148 μg/L). Radiology imaging showed hypermetabolic splenomegaly without lymphadenopathy. Bone marrow biopsy showed no evidence of lymphoma or other malignancy.